Simulasi Sistem Informasi Geografis (SIG) Pemantauan Posisi Kendaraan Via SMS Gateway - Hanifah, Raidah; Isnanto, R. Rizal; Christyono, Yuli (Departemen Teknik Elektro, Universitas Diponegoro, 2010)
Nowadays a vehicle position monitoring system has started to be built as its rising demand. A system with capability to trace the position of a vehicle by its owner or third party is well known as vehicle tracking system. This system provide many advantages, therefore in this Final Project a simulation of Geographic Information System (GIS) for Vehicle Position Tracking via SMS Gateway System is made. This system contains two main parts, those are device part and application part. Device part is simulated with a device simulation program. On the other side, application part will show the position information which sent by device par. The information is shown as a graphic with a map as the background. These two parts are developed by Delphi 7.0 programming language and MySQL 5.0 as a database storage. To show the map and mapping functions in this application, an additional program MapObject 2.0 is used. The function of SMS Gateway is connects the device part and application part, and software for this function is Gammu 1.25. This research results a simulation to monitor vehicle position system. The testing results show that this system works properly, and all functions work well as it purposes. The application part shows the position data from device part as pointed tracks in a map. Communication between GIS application part and device part via Gammu also works properly, with average interval of SMS sending time and receiving time is 17,8 seconds. Keyword : Geographic Information System (GIS), Position monitoring, SMS Gateway, Gammu.